If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-2(x-1)=-9x-26
We move all terms to the left:
-2(x-1)-(-9x-26)=0
We multiply parentheses
-2x-(-9x-26)+2=0
We get rid of parentheses
-2x+9x+26+2=0
We add all the numbers together, and all the variables
7x+28=0
We move all terms containing x to the left, all other terms to the right
7x=-28
x=-28/7
x=-4
| y+4=3/4 | | -3(k-5)=-9 | | 9.38=d+3 | | k/3=3.5 | | 5.4=2.3-0.6y | | (53)5x(53)11=(53)8x | | x/(10+x)=0.1 | | 2(y+3)-4y=-10 | | 5+3/5x=11 | | -y=45 | | 20=2f | | 0.10(x+60)+1.10x=42 | | -2g-3=11 | | 6r/5+1=1/20 | | 3x-6=0.12 | | -(10-k)=3(k+4) | | 0.6x-0.8=0.8(2x-1)-0.9 | | 5x^2+45x-18=0 | | d+3/4=8 | | -6=15+3c=-27 | | 5x^2+45x+18=0 | | b/2=24 | | -3(8-p)=p=4 | | 2.x^2+1=51 | | 7(2x-8)+3=15 | | 3g-7=3(g+2) | | 3z/10+9=2 | | -2(-5+4x)=30 | | 3x-4x=3x+6 | | 7(6-2a)=5(3a-1) | | 1/3=2n | | 9+10v/6=2 |